The Cultural and Scientific Life in QOM During the Abbasid Era (132-656 A.H/ 749-125 C.E): Historical Study - RIJ, ALAA HAMMAD; BAHAR, ABDULMUNAF AZZIZ (Al-Adab Journal, 2021)
QOM It lies along with an arid salty desert: From the north, it is bordered by the city of Al-Ray, to the south by Qashan, and from the west by Sawa. It was conquered by force by Abu Musa al-Ash’ari after the battle of Nahawand in the year (23 AH / 644 CE). The history of Qom was part of the struggle of the indignant powers over the Umayyads succession in the Islamic East, such as Mutrif ibn al-Mughira ibn Shahba when he deposed Abd al-Malik ibn Marwan. It also had a role in the Abbasids revolution, when they adopted it as their main position in their struggle with the Umayyads, so the Qummies were convinced of the illegality of the Umayyad and Abbasid succession in judgment. So they were showing their resistance in any way to the Abbasid succession. Thus, this city based its relationship with the Abbasid succession on constant hostility and rejection of them, which made the Abbasid succession warn of them and monitor their movements, and send armies to them when they departed from its obedience, as well as entering this city at an early period in Islamic history. The largest school of jurisprudence was established in it. Senior jurists and diligent people grew up in it. And it became one of the most important schools of jurisprudence in the Islamic world, after the school of Medina and the school of Kufa for the Shiite sect. It graduated many jurists, hadith narrators, and scholars in various Islamic sciences. One of the manifestations of the revival of Shiite thought was Moez al-Dawla al-Buaihi’s strengthening the position of the Shiites among other sects.